Synthesis of novel N-cyclopentenyl-lactams using the Aubé reaction - Shinde, Madhuri V.; Ople, Rohini S.; Sangtani, Ekta; Gonnade, Rajesh; Reddy, D. Srinivasa (Beilstein Journal of Organic Chemistry, 2015)
A novel and convenient method utilizing the Aubé reaction to access a new class of compounds that are similar to carbocyclic nucleosides is reported. The azido alcohol derived from Vince lactam undergoes the Aubé reaction with various cyclic ketones to give cyclopentenyl-substituted lactams. Upon dihydroxylation, this affords the N-cyclopentenyl-lactam compounds in racemic form. Given the numerous uses of nucleosides and related compounds, we were interested in the synthesis of carbocylic nucleoside mimics. The attempts and results are described herein.
Keywords: Aubé reaction; biological activity; carbocyclic nucleosides; cyclopentenylated lactams; cyclopentylated lactams